Guided reading : making it work - Schulman, Mary Browning; Payne, Carleen daCruz (New York : Scholastic Professional Books, 2000)
Ideas, resources, and a list of childrens' books that can be used to implement guided reading.
"Two teachers share their insights, strategies, and lessons for helping every child become a successful reader"--Cover.
Bibliography: p. 168-169.
Grades K-3.
Keywords: Reading (Primary); Children -- Books and reading; Teaching -- Aids and devices